A Half Squat Free weight and Machine Training Model to Increase Leg Muscle Strength and Mass - irkham, khafid (Journal of Physical Education and Sports, 2024)
The strength and mass of leg muscles are the important parts in forming an ideal body. Leg muscles are the part of the body that has the most and largest muscles compared to other parts of the body (presenting ± 50% of the entire front body muscle area). Achieving an ideal body requires several important aspects, one of which is a structured and consistent training program. This research aims to analyze the influence of half squat free weight and machine training models on leg muscle strength and muscle mass. This research method that is used is a quasi experiment with pre-test and post-test with two groups with 20 male samples aged 20-25 years. This research instrument uses a Leg Dynamometer to measure leg muscle strength and an InBody 270 scale to measure muscle mass. Data analysis used one way anova test, paired sample T-test. The result of T-test shows that half squat exercises using 1 kg of free weight and 8.4 kg of machine weight both result in an increase in leg muscle strength, with a significance value of 0.030 0.05, indicating that both exercises have some effect on this increase but that the half squat machine exercise is more effective. Half squat exercises using free weights (0.27 kg) and machines (0.3 kg) result in an increase in muscle mass with a significance level of 0.042-0.05, indicating that both exercises have an impact on the growth of muscle mass but that the half squat machine exercise is more effective.